Cannabis sativa and pregnancy: a review - Iran Augusto Neves da Silva; Daiana Aparecida Souza Lima; Sarah Gomes de Menezes Benevenuto; Mariana Matera Veras (Biotemas)
Cannabis sativa or marijuana is the most commonly used drug during pregnancy. Pregnancy is a period in which considerable physiological changes occur in the mother, and consequently, the fetus can be directly affected. Marijuana contains a range of medicinal or psychoactive components, the cannabinoids. The best known cannabinoid is tetrahydrocannabinol (?9-THC), a psychoactive drug capable of crossing the placental barrier and reaching the developing fetus. Chronic use of C. sativa in pregnancy may result in decreased uteroplacental perfusion, intrauterine growth restriction and behavioral disorders. Cannabinoids may cause some disorders in reproductive organs in users, which can harm the fetus. In one study, 4,000 pregnant women who used marijuana showed an increase in the incidence of pregnancy loss and low weight and small size for gestational age. In addition to low birth weight, the drug increases the risk of complications during childbirth and late cognitive development in infants. Many controversies revolve around the topic of C. sativa and its effects on human health, making it necessary to include the discussion of public policies on the release of the drug taking into account scientific evidence.